Implementation of Ethnic Identity in the Media Discourse (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-78-86The article aims to describe the specifics of the verbal implementation of ethnic identity in the Russian media discourse. The relevance of the work is due to the anthropocentric approach to linguistics, based on interdisciplinary connections with philosophy, cultural studies, literary studies, anthropology, etc., which significantly enriches the linguistic study of identity in the media discourse.The novelty of the research lies in the fact that the question of understanding media discourse as a verbal and informational continuum, in the space of which specific units are functioning, containing ethnocultural meanings and participating in the formation of the ethnic identity of a particular community. The significance for the theory of language is determined by the fact that extended and justified interpretations of the concepts “ethnicity” and “ethnic identity” are presented. The main parameters of the implementation of ethnic identity in the media discourse are established. The main lexical and semantic means that construct selfidentification in the modern media discourse were analyzed. And also, the accompanying markers of mass information discourse are highlighted.Within the framework of the structural-semantic approach, the following methods were used: discourse analysis, contextual, definitional, and continuous sampling. The results obtained can be used in a course of lectures on ethnolinguistics, sociolinguistics, and linguoculturology.Keywords: ethnicity, ethnic identity, self-identification, ethnic stereotypes, media discourse, media texts, mass information discourse.